Educators at university. A blended and problem based teaching model for the training course of "socio-pedagogical educator" - Maria Ranieri; Mario Giampaolo (Firenze University Press, 2018)
The paper presents a blended teaching model developed within a collaborative research project between university researchers and educators working within the Tuscan system of formal and non-formal education. On a theoretical level, the model is based on experiential learning, self-directed learning and social learning, which inspired at a macro-level the design of the course to encourage critical reflection, autonomous exploration or sharing of resources. At a micro-level, teaching design is guided by a problem based learning approach centered on a cycle of activation, documentation, application, research of resources, and final reflection. The authors illustrate how they implemented it within Moodle and conclude with some considerations on the possible developments of the model in terms of personalization.   Educatori all'università. Un modello di didattica blended e problem based per il corso di qualifica per educatori professionali socio-pedagogici Il contributo presenta un modello didattico blended sviluppato all'interno di un progetto di ricerca collaborativa tra ricercatori universitari ed educatori che operano nel sistema educativo Toscano formale e non formale. Sul piano teorico, il modello si basa su experiential learning, il self-directed learning e il social learning, che hanno ispirato a livello macro la progettazione del dispositivo blended per favorire riflessione critica, esplorazione autonoma o condivisione di risorse. La progettazione didattica a livello micro è guidata dall'approccio del problem based learning, centrato sul ciclo di attivazione, documentazione, applicazione, ricerca delle risorse e riflessione finale. Gli autori illustrano come hanno implementato questo ciclo in Moodle e concludono con alcune riflessioni sui possibili sviluppi del modello in termini di personalizzazione.